The influence of context-specific factors on the diffusion dynamics of onshore wind energy in Argentina: A constellation analysis of the wind energy diffusion dynamics in Argentina - Philipp Schaube (Wuppertal Institut für Klima, Umwelt, Energie, 2024)
This article aims to shed light on the contextual embeddedness of the diffusive dynamics of onshore wind energy in Argentina by employing the integrated MLP-TIS framework. Based on the methodology of constellation analysis, this paper analyses the various stages of development of onshore wind energy in Argentina since 1990. The objective is to investigate how exogenous dynamics have hindered or promoted the dissemination of wind energy in Argentina. Thereby, beyond the empirical findings, this study contributes to the growing body of sustainability transitions research. The results provide evidence of a variety of socio-technical niches across the five development phases of the focal TIS: pilot projects, self-generation by energy cooperatives, projects based on feed-in tariffs, state financed and operated wind farms, hydrogen production and compliance with legal requirements for large users. A key insight of this research is that the classification of the development phases of the technology trajectory in Argentina is particularly related to the effects of contextual factors. With the construction of South America's first wind farm in 1990, Argentina was the pioneer of wind energy in Latin America for almost a decade. This initial positive development was facilitated by a constellation of specific framework conditions: Stable exchange rates, liberalisation and privatisation of electricity markets, and subsequently wind energy as a business model for energy cooperatives. Moreover, since the 2000s, renewable energy has been perceived as part of the solution to the national energy crisis. However, the Argentine case also illustrates how, during later development phases, structural problems within the country, such as political instability or macroeconomic uncertainties, hampered access to international project finance and thus severely affected the further development of wind energy. Discontinuities in the basic orientation of the country's economic policy resulting from changes in government were identified as another relevant contextual factor.
urn:nbn:de:bsz:wup4-opus-86126
Keywords: 330